2018
DOI: 10.1002/bdm.2075
|View full text |Cite
|
Sign up to set email alerts
|

Some Metatheoretical Reflections on Adaptive Decision Making and the Strategy Selection Problem

Abstract: Organisms must be capable of adapting to environmental task demands. Which cognitive processes best model the ways in which adaptation is achieved? People can behave adaptively, so many frameworks assume, because they can draw from a repertoire of decision strategies, with each strategy particularly fitting to certain environmental demands. In contrast to that multi‐mechanism assumption, competing approaches posit a single decision mechanism. The juxtaposition of such single‐mechanism and multi‐mechanism appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 178 publications
1
16
0
Order By: Relevance
“…Put differently, if all models are able to discriminate a high percentage of decisions, the individuals may develop some preference for "how to choose" instead of changing the choice algorithm to fit the decision environment. This is consistent with theories of adaptive decision behavior [ 1 ] [ 2 ]. Second, we checked model redundancy; that is, the correlation of choice predictions among the algorithms.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Put differently, if all models are able to discriminate a high percentage of decisions, the individuals may develop some preference for "how to choose" instead of changing the choice algorithm to fit the decision environment. This is consistent with theories of adaptive decision behavior [ 1 ] [ 2 ]. Second, we checked model redundancy; that is, the correlation of choice predictions among the algorithms.…”
Section: Resultssupporting
confidence: 91%
“…In its rational aspiration, western culture has promoted the education of reason to dominate emotion but research has shown that such a dynamic is hard to sustain. From the cognitive perspective, it is currently accepted that human beings are able to adjust the depth and extent of their reasoning process according to tasks and situational demands [ 1 ] (See a recent review and reflection on adaptive decision making and strategy selection in [ 2 ]. In particular, the studies of boundedly rational decision algorithms, better known as fast and frugal heuristics [ 3 ] [ 4 ], have operationalized the notion of ecological rationality through simple decision algorithms that operate as a toolbox for decision makers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a large literature on heuristics and rules in decision making (Bettman et al, 1990;Brandstätter et al, 2006;Gigerenzer & Brighton, 2009;Gigerenzer, 2008;Gigerenzer & Gaissmaier, 2011;Gigerenzer & Todd, 1999a, 1999bMarewski et al, 2018Marewski et al, , 1993Maule, 1989;Price et al, 2013;Rieskamp & Hoffrage, 2008;Svenson, 1979Svenson, , 1998. Stanovich and West (2000), summarised a number of studies and suggested that biases in human cognition can depend on (1) performance errors, (2) computational limitations, (3) the wrong norm being applied by the experimenter and (4) a different interpretation of the task by the participant than intended by the researcher.…”
Section: Introductionmentioning
confidence: 99%